2015
DOI: 10.1074/jbc.m115.638361
|View full text |Cite
|
Sign up to set email alerts
|

K Domain CR9 of Low Density Lipoprotein (LDL) Receptor-related Protein 1 (LRP1) Is Critical for Aggregated LDL-induced Foam Cell Formation from Human Vascular Smooth Muscle Cells

Abstract: Background: LRP1 plays a major role in foam cell formation from human vascular smooth muscle cells (hVSMCs). Results: Antibodies generated against the C-terminal half of cluster II CR9 domain (Gly 1127 -Cys 1140 ) efficiently prevented hVSMC foam cell formation. Conclusion: CR9 is key for AgLDL binding and internalization. Significance: Our results open new avenues for treating vascular lipid deposition in atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…However, although all strains showed similar 125 I-Aβ 40 clearance, analysis of proteins expression showed SJL/J mice to have lower level of LRP1, which suggests species differences in the expression, trafficking, or degradation of this protein at the BBB. Interestingly, available studies showed a positive direct correlation between LRP1 expression and vascular lipid disposition in atherosclerosis, this correlation is consistent with our findings of low LRP1 level in SJL/J mice which are known to be resistant for the development of atherosclerotic lesions [20, 21]. …”
Section: Discussionsupporting
confidence: 93%
“…However, although all strains showed similar 125 I-Aβ 40 clearance, analysis of proteins expression showed SJL/J mice to have lower level of LRP1, which suggests species differences in the expression, trafficking, or degradation of this protein at the BBB. Interestingly, available studies showed a positive direct correlation between LRP1 expression and vascular lipid disposition in atherosclerosis, this correlation is consistent with our findings of low LRP1 level in SJL/J mice which are known to be resistant for the development of atherosclerotic lesions [20, 21]. …”
Section: Discussionsupporting
confidence: 93%
“…To generate DiI-oxLDL, a stock solution of the fluorescent probe: 1,1′-dioctadecyl-3,3,3′,3-tetramethylindocarbocyanine perchlorate (DiI, Molecular Probes Invitrogen, Carlsbad, CA) was prepared in DMSO and then added to the LDL solution to yield a final ratio of 1 μg of DiI/mg of oxLDL. The mixture was incubated for 18 h at 37 °C under light protection, as previously described [ 61 ]. Cells were incubated with HG or NG in M199 medium containing 0.2% SBF ( v / v ) for 72 h and with DiI-oxLDL (5 µg/mL) for the last 24 h. To test the specificity of uptake, the VSMC were treated with DiI-oxLDL and an excess of unlabeled oxLDL.…”
Section: Methodsmentioning
confidence: 99%
“…In general, modified LDLs can be bound and internalized by different cell surface receptors, such as scavenger receptors (LOX-1, scavenger receptor A (SRA), and CD36) and LRP1. The LRP1 receptor is the main one responsible for binding and internalizing aggLDL, whereas scavenger receptors can recognize other forms of modified LDLs [ 15 , 39 , 52 ]. However, LRP1 participation in the processing of other modified lipoproteins can not be discarded, since macrophages are able to incorporate diverse modified LDLs (mainly oxLDL), with LRP1 being necessary for these cells to become foam cells [ 53 ].…”
Section: Lrp1 In the Metabolic Syndromementioning
confidence: 99%
“…Based on its ability to exert complex and multi-molecular extra- and intracellular functions, LRP1 has been shown to be involved in MetS. In this way, this receptor plays a key role in the uptake and processing of modified and non-modified lipoproteins in different tissues, which is associated with the promotion of intracellular lipid accumulation occurring during dyslipidemia [ 15 , 16 , 17 ]. In glucose homeostasis, LRP1 has a regulatory action on the insulin receptor (IR) and GLUT4 activation [ 10 , 16 , 18 ], which has been strongly associated with insulin resistance developed during MetS.…”
Section: Introductionmentioning
confidence: 99%